2018
DOI: 10.1080/10888705.2018.1456925
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Attitudes Toward Animal Welfare-Friendly Products and Willingness to Pay: Exploration of Mexican Market Segments

Abstract: The study aim was to identify consumer segmentation based on nonhuman animal welfare (AW) attitudes and their relationship with demographic features and willingness to pay (WTP) for welfare-friendly products (WFP) in Mexico. Personal interviews were conducted with 843 Mexican consumers who stated they purchased most of the animal products in their home. Respondents were selected using a quota sampling method with age, gender, education, and origin as quota control variables. The multivariate analysis suggested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 54 publications
2
41
0
2
Order By: Relevance
“…The consumers in Santiago are willing to pay more for apparently welfare-friendly produced eggs such as those derived from free-range and cage-free hens. This is similar to results in European countries [4,11], or Mexico [14]. Interestingly, the current scientific evidence seems to point out that free-range or cage-free production system impose a greater welfare risk (diseases, environmental harness) than those in cage and more intensified system [6,15].…”
Section: Discussionsupporting
confidence: 83%
“…The consumers in Santiago are willing to pay more for apparently welfare-friendly produced eggs such as those derived from free-range and cage-free hens. This is similar to results in European countries [4,11], or Mexico [14]. Interestingly, the current scientific evidence seems to point out that free-range or cage-free production system impose a greater welfare risk (diseases, environmental harness) than those in cage and more intensified system [6,15].…”
Section: Discussionsupporting
confidence: 83%
“…Gender differences have been well established by Herzog [4], and most studies have found these effects regardless of country or culture. It would be an interesting aspect to further sample people from the urban-rural gradient, e.g., to compare city-dwellers with inhabitants from rural areas [35].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the explosive demand for pet food and the growth of the companion animal business, limited studies to date have shown the relationship between purchase attributes, purchase satisfaction, and animal welfare. [5,6] The purpose of this study is to analyze the determinants and factors influencing repurchase when consumers purchase food for companion animals, and verify the moderating effect of offline channels and online channels, which currently exhibit a rapid growth trend.…”
Section: Introductionmentioning
confidence: 99%